Looking for indicative magnetic resonance imaging signs of hippocampal developmental abnormalities in patients with mesial temporal lobe epilepsy and healthy controls. (22nd July 2020) - Labate, Angelo; Sammarra, Ilaria; Trimboli, Michele; Caligiuri, Maria Eugenia; Gambardella, Antonio
Abstract: Objective: To evaluate the frequency of qualitative features for hippocampal developmental abnormalities (HiDeA) definition on magnetic resonance imaging (MRI) in mesial temporal lobe epilepsy (MTLE) patients and healthy controls, highlighting which were more sensitive and specific to the epileptic syndrome. Methods: We enrolled 93 healthy controls and 187 MTLE patients. Among patients, 133 were MRI‐negative and 54 had hippocampal sclerosis (HS). Two blinded, trained investigators defined HiDeA if three signs were present, including at least one of the following: (1) globular hippocampal shape (HCS), (2) verticalized collateral sulcus, and (3) medial positioning of hippocampus (HCP). After evaluating the prevalence of HiDeA in MTLE and controls, we assessed the frequency of each sign. Then, we classified differences in type or number of HiDeA diagnostic features, calculating their sensitivity and specificity. Fisher exact test was used to assess statistical significance. Results: HiDeA was detected in 36 of 187 MTLE cases (19.25%) and in eight of 93 (8.6%) controls. In particular, HiDeA was present in 25 of 133 (18.8%) patients with MRI‐negative MTLE. Among all visual criteria here considered, HCS showed higher sensitivity both in the MRI‐negative MTLE group (88%) and in the HS‐MTLE group (91%). HCP, thickened subiculum, and reduction of the upper horizontal portion of the parahippocampal gyrus (HCTH) signs demonstrated a 100% specificity in both groups. In healthy controls, HCS was confirmed to have the highest sensitivity (100%), whereas HCP showed the highest specificity (98.8%). All these criteria were statistically associated with HiDeA. Electroencephalographic focus was concordant with the HiDeA side in 52.2% of MTLE patients. An association was not found among signs of HiDeA and treatment responsiveness. Significance: We identified characteristic signs of HiDeA, such as HCTH or HCP, differentiating HiDeA features between MTLE and healthy controls. The identification of sensitive and, more importantly, specific criteria of HiDeA could be helpful to make a more confident visual diagnosis.